Um estudo pancrônico da voz reflexiva em perspectiva construcional - Barros, Déborah Magalhães de (2016)
This research describes and analyzes the reflexive voice in different historic moments of the Portuguese formation, in order to prove a change in the shape of the grammar domain on Contemporary Brazilian Portuguese (PB). This research was motivated by the pronominal nonmarking in the prototypical reflexive voice in (PB), mainly, in the spoken variety in Goiás. In the center of this change is the concurrence among uses in the prototypical reflexive voice or morphologically marked (VRM), defined by the presence of the reflexive pronoun, and the reflexive voice non-marked (VRNM), elaborated without the pronoun mark. We intend to understand the linguistics and discursive processes correlated on this change. The Functional Linguistics Centered in the Use, more specifically, the Construction Grammar, gave the theoretical base for this analysis, with the highlights for the contribution of Bagno and CassebGalvão (in press), Bybee (2010, 2015), Croft (2001), Croft and Cruse (2004), Givón (1984, 1990, 1992, 1995), Goldberg (1995, 2006), Hopper and Thompson (1980), Langacker (2013), Tomasello (2003, 2008, 2009) and Traugott (2008) and Traugott and Trousdale (2013). Authors such as Barros (2011), Benveniste (2005), Bertoque (2010, 2014), Camacho (2000, 2002, 2003) and Kemmer (1993, 1994), among others which gave aids to the definition of the characterization of the reflexive voice. The Construction Grammar is a theoreticalmethodological approach that considers the language in use and acknowledges the existence of a narrow relation between the language structures and the updated use by the speakers in real contexts of communication. In this perspective, the language arises from the use and organizes itself in constructions, linguistics unities built by the pairing of form and meaning. The reflexive voice is considered, thus, member of a constructional voice network, a multifactorial domain whose conceptual base is an abstract scheme influenced by transitivity and the clausal ordination. Data analysis is predominantly qualitative and panchronic, contemplating different historic moments of the formation of Portuguese from the Vulgar Latin to Modern Portuguese and the contemporary PB (XX and XXI). The results of the analysis indicate changes in the structure of the reflexive voice and semantic features of the agent and the patient, which has led to transformation in constructional voice network, amplified by semantic-pragmatic pressures, which is a case of constructionalization.